Spain : Staff Report for the 2011 Article IV Consultation; Public Information Notice; Statement by the Staff Representative; and Statement by the Executive Director for Spain. (IMF Staff Country Reports; Country Report ;, 2011)
A decade of strong expansion in the Spanish economy led by a credit-fueled housing boom was hit by three major shocks. The policy response to Spain's economic challenges has been strong and wide-ranging, helping to strengthen market confidence. A decisive implementation of the envisaged financial sector reform strategy would help allay lingering market concerns. A bold strengthening of labor market reforms is needed to substantially reduce unacceptably high unemployment. Further progress needs to be made on enhancing competition in nontradable sectors.